Duodenal ampullary neuroendocrine tumor, high risk gastrointestinal stromal tumor, and gastric leiomyoma in a patient with neurofibromatosis type 1: a rare case report and literature review - Yin, Xiaonan; Yang, Hongxin; Yin, Yuan; Zhang, Bo (Frontiers in Oncology, 2026)
Neurofibromatosis type 1 (NF1), an autosomal dominant disorder resulting from mutations in the NF1 tumor suppressor gene, predisposes affected individuals to diverse benign and malignant neoplasms. We herein report a rare case of a 61-year-old female NF1 patient presenting with a unique combination of four synchronous or metachronous tumors: a duodenal ampullary neuroendocrine tumor (NET, Grade 2), a high-risk gastrointestinal stromal tumor (GIST) of the small intestine, a previously resected gastric leiomyoma, and cutaneous neurofibromas. Preoperative evaluation included endoscopy, endoscopic ultrasound, contrast-enhanced CT, and MRI, which localized the lesions and assessed their morphological features. The patient underwent pancreaticoduodenectomy and partial small bowel resection, achieving complete tumor resection. Genetic testing identified a germline NF1 mutation (p.Y2182*). No adjuvant therapy was administered due to the absence of residual disease and actionable mutations. This case highlights the broad tumor spectrum in NF1 and underscores the importance of comprehensive imaging, multidisciplinary management, and genetic testing for optimal outcomes.